2019
DOI: 10.1515/pjbr-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Using the humanoid robot Kaspar in a Greek school environment to support children with Autism Spectrum Condition

Abstract: Previous studies conducted with the humanoid robot Kaspar in the UK have yielded many encouraging results. This paper examines the influence of conducting play sessions with Kaspar on the social and communication skills of children diagnosed with Autism Spectrum Condition (ASC) and suggests possible ways for using the robot as a (therapeutic) tool in a Greek school for children with special needs. Over a period of 10 weeks 7 children took part in a total of 111 individual play sessions with the Kaspar robot. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
0
13
0
2
Order By: Relevance
“…Such systems can be used to augment therapeutic efforts by parents and interventionists. Existing, albeit limited, evidence suggests preliminary efficacy of employing SAR to increase frequency of utterances (Karakosta et al, 2019; Kim et al, 2013), joint attention (Warren et al, 2015), and imitation (Karakosta et al, 2019) in ASD. Though the mechanisms through which SAR might facilitate learning and performance in children with ASD are not well understood, robots' combination of object‐like simplicity and predictable, human‐like social behaviors could make them meaningful agents for the facilitation of interventions in children with developmental conditions such as ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems can be used to augment therapeutic efforts by parents and interventionists. Existing, albeit limited, evidence suggests preliminary efficacy of employing SAR to increase frequency of utterances (Karakosta et al, 2019; Kim et al, 2013), joint attention (Warren et al, 2015), and imitation (Karakosta et al, 2019) in ASD. Though the mechanisms through which SAR might facilitate learning and performance in children with ASD are not well understood, robots' combination of object‐like simplicity and predictable, human‐like social behaviors could make them meaningful agents for the facilitation of interventions in children with developmental conditions such as ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Overall findings underline the possibility to improve communication, psychomotor functions, and social skills, with particular regards to unprompted imitation (i.e., imitation of poses, movements, and facial expressions), prompted speech, and gesture recognition. Furthermore, a positive increasing trend has also been found in prompted imitation and unprompted speech [53] and improvements in visual perspective taking have been reported in children with moderate to high-functioning ASD [54].…”
Section: Study Results Organized By Robot Employedmentioning
confidence: 87%
“…Overall, studies showed mixed results, but most of the selected reports found improvements in social skills. From the point of view of behavior, children particularly improved in turn taking [30,55], eye gaze [32][33][34]44,58], imitation [30,53], play skills, fostering collaboration [46], and communication [53] thanks to the interaction with robots as compared to human agents. Moreover, a reduction in autistic behaviors [34,46] and an increase in adaptive ones were also found [33].…”
Section: Study Resultsmentioning
confidence: 99%
“…While those studies with Kaspar were conducted independently of our research team at the University of Hertfordshire, our team has also conducted a number of other more controlled studies in schools. This includes a study using the robot in a different cultural context, namely, in a Greek school [76] as well as studies investigating how Kaspar can teach children with autism about visual perspective taking, for examples see [29], and how the robot can learn from interactions with children with autism [77]. Moreover, Kaspar was used independently by a clinician in the University Children's Hospital-Skopje, Macedonia, and case studies with children with severe autism are provided in [78].…”
Section: Continuation Of the Workmentioning
confidence: 99%